2016
DOI: 10.1108/nfs-11-2015-0146
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal weight on pregnancy outcomes: a systematic review

Abstract: Purpose The nutritional status of a woman before and during pregnancy is important for a healthy pregnancy outcome. The increasing prevalence of maternal overweight and obesity worldwide has become a problem of concern among public health professionals. The purpose of this paper is to review the evidence regarding the impact of maternal weight on pregnancy outcomes to facilitate the provision of evidence-based information to pregnant women during antenatal clinics in Ghana. Design/methodology/approach A sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 45 publications
1
16
0
1
Order By: Relevance
“…Maternal obesity can substantially interfere the fetal development and determines the long term health of the offspring [30]. It is also a major risk factor for gestational diabetes, preeclampsia and pregnancy-induced hypertension in women [31,32]. Our study demonstrated a higher prevalence of hypertension in Gandaki province and the lower in Sudurpaschim province that is in line with national findings carried out in the general population [33].…”
Section: Characteristics Mean Number Clustering Of Ncd Risk Factors Asupporting
confidence: 90%
“…Maternal obesity can substantially interfere the fetal development and determines the long term health of the offspring [30]. It is also a major risk factor for gestational diabetes, preeclampsia and pregnancy-induced hypertension in women [31,32]. Our study demonstrated a higher prevalence of hypertension in Gandaki province and the lower in Sudurpaschim province that is in line with national findings carried out in the general population [33].…”
Section: Characteristics Mean Number Clustering Of Ncd Risk Factors Asupporting
confidence: 90%
“…The construction of this variable was based on questions in IDHS 2012. The low birth weight of new born baby was considered those who were delivered with the weight less than 2500 gram [15]. If the infant was less than 2500 gram then coded as 1 for "low birth weight" while else coded as 0.…”
Section: Methodsmentioning
confidence: 99%
“…The multilevel logistic model was implemented to predict the probability of the occurrence of LBW by taking into account the effect of family wealth levels and the region effects. The region and family wealth level were considered as the multilevel parameterdue to different geographical regions of the Indonesia, while the family wealth level may be related to the purchasing power of mother and dietary patterns which results in pregnancy and weight of baby [15,16]. The hypothesis was considered statistically significant if p-values were less than 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Maternal underweight increases the risk of intra uterine growth restrictions. Over the past 10 years, trends in weight of women age 15 to 49 has changed towards overweight and obesity [12]. In 2014, the Ghana statistical service reported that 25% of women are overweight and 15% are obese [13].…”
Section: Introductionmentioning
confidence: 99%